Mission as "being with" in the context of the COVID-19 pandemic in South Africa - Knoetze, Johannes J. (HTS teologiese studies, 2023)
This research investigated the impact measures (such as lockdowns) used to combat the spread of the coronavirus disease of 2019 (COVID-19) have on the church’s mission. When people face travel and assembly restrictions, the church as a community of witnesses testifying and participating in Christ’s work risks is being neutralised, and its presence weakened. What then does mission as ‘being with’ look like in these situations? Is faithful presence something one can turn on and off at will depending on the situation? If faithful presence was no more, what then was the impact of such absence on the church’s mission? These questions underscore the relevance of this research which sought to ascertain the impact the COVID-19 pandemic lockdown had on the church’s mission. The crucial area this research sought to explore are the lessons from the COVID-19 lockdown that will help the church prepare for future pandemics which scientists say are inevitable. The research made use of a qualitative interview method to discover the meaning of ‘being with’ in the context of the COVID-19 lockdown. The results revealed six attributes of a missional church. Based on these attributes, the research recommends a seven-step process to prepare the church for possible future pandemics.Contribution: This research has provided the church with an opportunity to shift from being ‘inward-looking’ to a church that is community focused, a church that prepares, trains and equips its adherents for the work of ministry in their own communities such that the work of ministry continues with or without gatherings.